Can parental consanguinity be a risk factor for the occurrence of nonsyndromic oral cleft?. (August 2019) - Silva, Carolina Maia; Pereira, Maria Carolina de Moraes; Queiroz, Thaís Bernardes de; Neves, Lucimara Teixeira das
Abstract: Background: The cleft lip with or without palate is the most common congenital craniofacial anomaly, presenting prevalence that varies between different ethnicities. It presents a complex and multifactorial etiology which involves genetic and environmental factors. Regarding family history, some studies have observed a significant association among parental consanguinity and orofacial clefts. Aims: To investigate if there is an association between parental consanguinity and the occurrence of oral cleft in the offspring. Study design: Retrospective, cross-sectional, quantitative case-control study. Subjects: Case group - parents of subjects with nonsyndromic oral cleft ( n = 746). Oral cleft was classified in the following group: cleft lip only - CLO (complete or incomplete, unilateral or bilateral); complete cleft lip and palate - CLP (unilateral or bilateral); and, cleft palate only - CPO (complete or incomplete). Control group - parents of subjects without clefts or other anomalies ( n = 502), totaling 1248 subjects. Outcome measures: Fisher's exact test was used to compare the consanguinity rates observed between the two groups ( p < 0.05 for statistically significant differences). Results: A positive consanguinity rate of 2.68% was observed in the case group and 0.79% in the control group. This difference found between the groups was statistically significant ( p = 0.02). The most frequent degree of kinship in cases of consanguineous marriages, in both groups, was between first cousins. The most frequent types of clefts in the offspring were also the cleft palate only and the cleft lip only. Conclusion: In the study population, parental consanguinity was associated with the occurrence of nonsyndromic oral cleft, and may be considered an isolated risk factor in this population. Highlights: Consanguineous marriages have been associated with nonsyndromic orofacial clefts. A statistically significant difference was found when we compared the rates obtained in case-control groups ( p = 0.030). Information regarding consanguineous marriages help to determine one of the risk factors for nonsyndromic orofacial clefts.